Mafia infiltration, public administration and local institutions: a comparative study in Northern Italy - Dagnes, Joselle (European journal of criminology, 2020)
Nuanced explanations of the factors underpinning the mafia’s movements across territories have recently been proposed. However, more light must be shed on the mechanisms through which mafiosi try to infiltrate the legal economy in non-traditional territories. Accordingly, this study aims to micro-found interactions and exchanges that mainly involve mafiosi, politicians and economic actors in expansion areas. Focusing on the local level, we will show how the misuse of several administrative tools generates a profitable opportunity structure for mafiosi. To this end, we present an in-depth comparative case study of three events involving the construction industry that took place in Northern Italy. The main findings show that: (i) mafiosi are skilled at smoothing social relations, enlarging and consolidating opaque networks predating their arrival; (ii) they give rise to different types of mutual exchanges and network structures.